Efek Antioksidan dari Ekstrak Biji Petai Cina (Leucaena leucocephala L.) pada Tikus Putih - Fatty Nurhasanah; Syamsudin Syamsudin (Fakultas Farmasi Universitas Pancasila, 2005)
The study deals with the examination of the antioxidative effect of a Leucana leucocephala L. seed extract on diabetic rats induces with streptozotosin. The rats were divided in to 6 groups, each consisting of 5 rats i.e. group 1: normal, group 2: control (chlorpropamide), group 4: low dose of Laucaena seed extract 0,5/kg BW and group 6: high dose of Laucaena seed extract 1 g/kg BW. The malon dialdehyde (MDA) and superoxid dismutase (SOD) contents were analyzed by ANOVA and continued with the ttest. The result obtained shows that an increase of SOD could be observed by a Laucaena seed extract of resp 0.25;0.5 and 1 g/kg BW.